2019
DOI: 10.5222/head.2019.068
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Dyadic Adjustment and Quality of Life in Infertile Couples

Abstract: İnfertilite; biyolojik, ruhsal, etik, sosyal ve ekonomik problemleri beraberinde getiren kültürel ve dinsel yönleri olan önemli bir sorundur. Birçok boyutu bulunan infertilitenin tüm dünyada yaklaşık olarak 50-80 milyon çifti olumsuz etkilediği tahmin edilmektedir. Başka bir deyişle Türkiye'de evli 6 kadından biri, dünyada ise ortalama her 10 kadından biri bu sorunu yaşamaktadır. Bu sorun sadece kadınları değil, onların ailelerini, eşlerini, eşlerinin ailelerini ve yakın çevrelerindeki birçok kişiyi de etkilem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Previous research investigating the association between infertility and conjugal harmony yielded diverse outcomes. Some studies suggested that infertility negatively impacts their relationships for women and they showed less dyadic adjustment than men (Zeren et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research investigating the association between infertility and conjugal harmony yielded diverse outcomes. Some studies suggested that infertility negatively impacts their relationships for women and they showed less dyadic adjustment than men (Zeren et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This study investigated the effect of care given to women receiving infertility treatment under the guidance of LCM on their fatigue, sleep quality, depression, and perceived social support levels. Infertility is the major crisis in the life of most couples (Zeren & Gursoy, 2019). The infertility treatment process is physically painful, emotionally stressful, and economically compelling for couples (Kirca & Pasinlioglu, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This study investigated the effect of care given to women receiving infertility treatment under the guidance of LCM on their fatigue, sleep quality, depression, and perceived social support levels. Infertility is the major crisis in the life of most couples (Zeren & Gursoy, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, couples who have failed infertility treatment experience less social support, more sexual dissatisfaction, and an increased risk of suicide (Doyle & Carballedo, 2014;Zeren, Gursoy & Colak, 2019). However, infertile couples with higher levels of education, higher income, and shorter infertility periods are more likely than their infertile counterparts to be more satis ed with their marital relationships' problems (Rutstein & Shah, 2004;Zurlo et al, 2018;Boivin, Takefman, & Braverman, 2011).…”
Section: Introductionmentioning
confidence: 99%